Factors that Influence Shared E-Scooter Usage Intentions on University Campus - Waranpong Boonsiritomachai; Ploy Sud-On (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2024)
In response to increasing environmental awareness, universities have introduced shared e-scooters for staff and students. However, usage remains low, indicating a disparity. This study investigates factors influencing Kasetsart University (Bangkok, Thailand) students' intentions to use shared e-scooters. A Likert-scale survey gathered data from 424 qualified respondents, and multiple regression analysis identified six factors: social norms, environmental concerns, infrastructure quality, perceived convenience, safety concerns, and cost. Environmental concerns and cost had no significant impact on students' intentions to use e-scooters. This study helps stakeholders, including the student council, e-scooter suppliers, and university administration, understand student demands and formulate suitable policies for on-campus mobility. Boosting e-scooter adoption can also justify the university's investment. However, the study is limited by its exclusive focus on student perspectives. Future research should integrate qualitative methods alongside quantitative approaches for a comprehensive understanding and better policy and service development for e-scooter adoption. Keyword: intention to use; shared e-scooter; theory of planned behavior